PENGARUH TATA KELOLA PERUSAHAAN DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA (Studi Empiris Perusahaan yang Melakukan IPO di Bursa Efek Indonesia Tahun 2021-2023) - Rizky Ramadhan; Puji Harto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of corporate governance and investment opportunity set (IOS) on earnings quality, by considering control variables such as company size, profitability, and cash holding. The independent variables tested in this study are board diversity, executive compensation, interlocking directorship, and investment opportunity set (IOS), while earnings quality serves as the dependent variable. This study focuses on companies conducting Initial Public Offerings (IPOs) on the Indonesia Stock Exchange (IDX) in the period 2021 to 2023. The research sample was taken using a purposive sampling method, resulting in 292 observations obtained from company prospectuses, financial statements, and published annual reports. Data analysis was carried out using multiple linear regression after conducting classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity tests. The results of the study indicate that board diversity and investment opportunity set (IOS) have a significant negative effect on earnings quality, while executive compensation and interlocking directorship do not show a significant effect on earnings quality. As for the tested control variables, company size and profitability show a significant negative effect on earnings quality. Meanwhile, cash holding does not have a significant effect on earnings quality.